Extração, estabilidade, reologia e higroscopicidade do corante de pitaya (Hylocereus costaricencis) - SOUSA, Erika Milene Pinto de (Universidade Federal do Pará, 2017)
With the advancement of new technologies the natural dyes market is expanding with the purpose to replace the artificial dyes, harmful to health. Natural dyes from fruit, give the product a more natural appearance, opposed what occur with synthetic tones. In this context, perform out extraction of dragon fruit dye contained in the fruit pulp, by immersion in distilled water, then makes up the physical and physico-chemical characterization of pulp, the study of the stability at light and temperature of concentration from betacyanin and dye color, quantifying the betacyanin content by UV spectrophotometry and color by colorimetric tristimulus using the CIE L * a * b *. Also evaluates up the rheological behavior of pulp pitaya diluted in distilled water at a ratio of 1: 1 by means of mathematical models with the support of ReoWin and Statistica 7.0 program. Finally, the study it’s made a hygroscopicity study obtained by freeze-drying at different concentrations maltodextrin, also analyzing the pure dye by verifying through of sorption curves optimal storage conditions for dragon fruit dye.